Collaborative Autoethnography: Best Practices for Developing Group Projects - Elizabeth Robertson Hornsby; Allyson Davis; James C. Reilly (Park University, 2021)
Collaborative Autoethnography (CAE) is an emerging practice that combines group interaction with qualitative research. Group projects are often deployed in course design to maximize the value of collaborative learning environments. Using existing scholarship, we describe best practices for group projects that apply principles of CAE. To advance the premise of the paper beyond descriptive summaries of pedagogical inquiry, we utilize a best practices mechanism to present a coherent guide for project collaborators to use in various classroom settings. The best practices proposed are research validated by existing CAE and project management literature.